Two phase dynamic model for gas phase propylene copolymerization in fluidized bed reactor - Shamiri, A.; Hussain, Mohd Azlan; Mjalli, F.S. (2011)
Porous materials have gained wide use in high level engineering structures due to their high stiffness/weight ratio, good energy absorption properties, etc. Frequently, thermal behavior is also an issue of concern and optimized multifunctional thermo-mechanical responses are sought for. This paper presents the application of a hybrid two-stage method for achieving an optimized layout of periodic truss-like structures in order to obtain a good compromise between thermal and mechanical elastic properties. The first stage employs a derivative free optimization method, which explores the design space, not getting trapped by local minima. The second stage uses a derivative based optimization algorithm to perform a refinement of the solution obtained in the first stage.